Experimental study of an argon-hydrogen Z pinch plasma radiation source - Shishlov, A.V.; Baksht, R.B.; Labetsky, A.Yu; Oreshkin, V.I.; Rousskikh, A.G.; Fedunin, A.V.; Chaikovsky, S.A.; Kokshenev, V.A.; Kurmaev, N.E.; Fursov, F.I. (IEEE transactions on plasma science, 2002)
Experiments with Ar-H/sub 2/ double gas puffs have been conducted on the GIT-12 generator at the current level of 2.1-2.4 MA and 250-350 ns implosion times. The argon-hydrogen mixture was used as a working medium in the outer shell of a double gas puff. The goal of the experiments was to verify whether the use of the argon-hydrogen mixture in the outer shell can improve the stability of a double gas puff implosion and provide increased argon K-shell radiation yields. The experiments showed that hydrogen admixture results in the change of implosion dynamics: decreased implosion velocities and compression ratios. The experimental data does not allow a conclusion that the use of an Ar-H/sub 2/ mixture in the outer shell of a double gas puff significantly improves the implosion stability. An increase in the hydrogen percentage in the outer shell leads to a decrease in plasma density and temperature, and as a result, reduced K-shell radiation yields and powers.